ENHANCING STUDENTS’ SPEAKING SKILL THROUGH DEBATE TECHNIQUE - Widyaningsih, Titik Lina (STKIP PGRI TULUNGAGUNG, 2016)
Speaking is an ability that is taken for granted, learned as it is through process of socialization through communicating. It seems very important because by mastering speaking skill, people can carry out conversations with others, give the ideas and exchange the information with others. In the third semester of English Department, the students get difficulties to speak English well. They lack of mastering the component of speaking. They only have a little chance to practice speaking English out of class because most of their friends speak Indonesian. Students’ speaking problem can be solved by giving a lot chance to them for practicing English either in the classroom or out of classroom. Practicing speaking English in the classroom should be interested with appropriate technique in order to improve students speaking skill. One of technique can be used in teaching speaking is debate. This research was aimed to improve the third Semester Students of English Department at STKIP PGRI Tulungagung through debate technique. This research was classroom action research done in two cycles. The data collection was done using observation and test. The participants of this research were 24 students. The result of this research showed that using debate technique can improve students’ speaking skill. This was proven by students’ test score that improved in every cycle. In the first cycle, the students’ average score was 71 and in the second cycle students got 82. Thus, debate is an appropriate technique used to improve students’ speaking skill.